Fluorescein-based dyes are not valid reporters of oxidative stress in bacteria, and conclusions based on their use must be reconsidered - Sergey Korshunov; James A. Imlay (Proceedings of the National Academy of Sciences, 2025)
Dihydrodichlorofluorescein derivatives have been employed as reporters of intracellular reactive oxygen species (ROS) in innumerable studies. Their use in bacteria has led investigators to conclude that a wide array of cellular stresses owe their toxicity to the formation of ROS. However, in the present study we find that this dye reacts too poorly with physiological concentrations of superoxide or hydrogen peroxide to signal their presence, and that lethal doses of hydroxyl radicals are dispersed among too many intracellular targets for the dye to be detectably oxidized. Instead, common redox moieties inside the cell—including flavins, quinones, and metal centers—capably oxidize the dye. Indeed, the dye is oxidized as rapidly inside anaerobic cells as inside aerobic ones, refuting any involvement of ROS. The ability of diverse stresses to increase the dye signal derives from the fact that both the reduced and oxidized forms of the dye are continuously exported by protonmotive force-driven pumps. Any stress or growth condition that diminishes the cellular energy charge has the effect of slowing these pumps and thereby causing an increase in the intracellular dye signal. Therefore, the unfortunate combination of ROS-independent dye oxidation plus stress-driven metabolic slowdowns have led investigators to conclude incorrectly that diverse stressors generate ROS. Those conclusions, including ones involving clinical antibiotics, must be reconsidered.